i can help!
lets say the distance they traveled on the first day is x. if the distance traveled on the second day is 3/4 of the distance traveled on the first day, it can be expressed as x(3/4), or 3x/4. if the distance traveled over both days is y, then y=x+(3x/4).
since the equation essentially just expresses a ratio between the distance traveled over the first vs second day, the total distance can be basically anything.
for example, if they travel 1 mi on the first day (x=1) the equation looks like this: y=1+(3/4). then y=7/4mi. but its just as valid to say x=2mi. then y=2+(3(2)/4), and then the total distance (y) is 7/2 mi